Activity of Protease-Activated Receptors in Primary Cultured Human Myenteric Neurons - Kugler, Eva M.; Mazzuoli, Gemma; Demir, Ihsan E.; Ceyhan, Gueralp O.; Zeller, Florian; Schemann, Michael (Frontiers in Neuroscience, 2012)
Activity of the four known protease-activated receptors (PARs) has been well studied in rodent enteric nervous system and results in animal models established an important role for neuronal PAR2. We recently demonstrated that, unlike in rodents, PAR1 is the dominant neuronal protease receptor in the human submucous plexus. With this study we investigated whether this also applies to the human myenteric plexus. We used voltage sensitive dye recordings to detect action potential discharge in primary cultures of human myenteric neurons in response to PAR activating peptides (AP). Application of the PAR1-AP (TFLLR) or PAR4-AP (GYPGQV) evoked spike discharge in 79% or 23% of myenteric neurons, respectively. The PAR1-AP response was mimicked by the endogenous PAR1 activator thrombin and blocked by the PAR1 antagonists SCH79797. Human myenteric neurons did not respond to PAR2-AP. This was not due to culture conditions because all three PAR-APs evoked action potentials in cultured guinea pig myenteric neurons. Consecutive application of PAR-APs revealed coexpression (relative to the population responding to PAR-APs) of PAR1/PAR2 in 51%, PAR1/PAR4 in 43% and of PAR2/PAR4 in 29% of guinea pig myenteric neurons. Our study provided further evidence for the prominent role of neuronal PAR1 in the human enteric nervous system.